Analisis Kemudahan Penggunaan Aplikasi Salak Deli Dengan Menggunakan Metode TAM - Hotnida Br. L. Tobing; Monika Theresia Togatorop (Bulletin of Information System Research, 2024)
Information systems in technology are now familiar to the public so that they have become the most important aspect of people's lives. The satisfaction felt by the community is very influential on the information system because it can trigger people to accept an information system that is used. This study was conducted to determine the public's assessment of the information system by providing a questionnaire to the community so that the public can assess how the information system is and will be analyzed using the TAM method. In the TAM method, the variables to be used consist of perceived easy of use with a percentage of 96.5% and perceived usefulness of 93%, actual use presentation of 96%, attitude toward using percentage of 94%. By showing that the people of Patumbak are satisfied with the SALAK DELI application.